Manejo de la anemia normocítica normocrómica con eritropeyetina beta vs eritropeyetina alfa en los pacientes con enfermedad renal crónica terminal que se encuentran en el centro de Diálisis Cener-Quito en el periodo octubre 2013 a marzo del 2014. - Guzmán Ch., Luz Gabriela. (2014)
The detection and treatment of anemia due to chronic kidney disease can preventor improve various adverse conditions associated with this disease, such as left ventricular hypertrophy, while maintaining quality of life , reduce morbidity , decrease the need for red blood cell transfusions and generally improve the possibility of rehabilitation of the patient , reducing the risk of death. The therapeutic vailability of recombinant human erythropoietin has introduced dramatic changes in the quality of life of patients with chronic kidney disease, has proved effective in correcting the anemia. Currently we have differentery thropoiesis –stimulating factors: epoetin alfa and epoetin beta short life, darbepoetin and methoxy . Our population with chronic kidney disease is in treated in different dialysis epoetin alfa and short-acting beta, so we need to know what kind of erythropoietin our patient responds better, less dose, less adverse effects maintaining hemoglobin parameters recommended by the societies of nephrology. Thus made after studying grievant field say that prescribing erythropoietin beta and alpha short life in patients with chronic kidney disease on hemodialysis and equivalent doses often maintain hemoglobin level above 11 g / dl recommended by the international standards. Is clinical response using beta as erythropoietin alfa is similar to the management of anemia in patients on hemodialysis.